AN ANALYSIS OF THE MAIN CHARACTER THROUGH FEMINISM APPROACH IN THE DA VINCI CODE NOVEL - Suwandarsih, Eni; Agustin, Ria Kamilah (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2023)
The study aimed to analyze the main character by using feminism approach in the novel The Da Vinci Code. The study concerns to find out the feminism theory based on Julia Kristeva’s. This study applied descriptive qualitative method in the data collected by library techniques namely document and analyzing the data used data reduction, data display, and data verification. The findings showed that characteristic of the main character is an educated women, a brave woman and a powerful women. The findings shows the 3 types of feminism, liberal, radical, and cultural. The findings show that The Holy Grail symbolizes the quest to retrieve the time-honored “Feminism Worship” and to promote the self-consciousness of women. Keywords: Main character, Feminism approach, The Da Vinci Code